Silk fibroin films with embedded magnetic nanoparticles: evaluation of the magneto-mechanical stimulation effect on osteogenic differentiation of stem cells. Issue 39 (23rd September 2022) - Del Bianco, Lucia; Spizzo, Federico; Yang, Yuejiao; Greco, Gabriele; Gatto, Maria Laura; Barucca, Gianni; Pugno, Nicola M.; Motta, Antonella
Abstract : By combining physical characterization data, in vitro biological tests and numerical calculations, we unveil the magneto-mechanical effect promoting the osteogenic differentiation of stem cells grown on silk fibroin films with magnetic nanoparticles. Abstract : We report about a biomaterial in the form of film ∼10 μm thick, consisting of a silk fibroin matrix with embedded iron oxide superparamagnetic nanoparticles, for prospective applications as bioactive coating in regenerative medicine. Films with different load of magnetic nanoparticles are produced (nanoparticles/silk fibroin nominal ratio = 5, 0.5 and 0 wt%) and the structural, mechanical and magnetic properties are studied. The nanoparticles form aggregates in the silk fibroin matrix and the film stiffness, as tested by nanoindentation, is spatially inhomogeneous, but the protein structure is not altered. In vitro biological tests are carried out on human bone marrow-derived mesenchymal stem cells cultured on the films up to 21 days, with and without an applied static uniform magnetic field. The sample with the highest nanoparticles/silk fibroin ratio shows the best performance in terms of cell proliferation and adhesion. Moreover, it promotes a faster and better osteogenic differentiation, particularly under magnetic field, as indicated by the gene expression level of typical osteogenic markers. These findings are explained in light of the results of the physical characterization, combined with numerical calculations. It is established that the applied magnetic field triggers a virtuous magneto-mechanical mechanism in which dipolar magnetic forces between the nanoparticle aggregates give rise to a spatial distribution of mechanical stresses in the silk fibroin matrix. The film with the largest nanoparticle load, under cell culture conditions ( i.e. in aqueous environment), undergoes matrix deformations large enough to be sensed by the seeded cells as mechanical stimuli favoring the osteogenic differentiation.